The Role of the Police in Managing Social Conflict Between Communities: An Approach Based on Islamic Values and Socio-Cultural Wisdom - Jolmadi Jolmadi; Masnun Masnun; Suprapto Suprapto; Iwan Fitriani (Journal of General Education and Humanities, 2026)
Social conflicts between communities in Mataram City often escalate due to poor emotional control and strong group solidarity, requiring a more humane, context-sensitive approach to resolution. This study aims to analyze the role of the police in managing social conflicts by integrating Islamic values and socio-cultural wisdom, and to propose an integrated model of conflict management. This study employs a qualitative case study approach, with data collection techniques including direct observation at the incident site, in-depth interviews with police officers, government officials, and community leaders, and documentation of social conflicts. Informants were selected through snowball sampling, and data analysis used the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The research findings indicate that conflicts that initially have an individual nature can escalate into communal conflicts. The role of the police is not merely that of law enforcers, but also as social facilitators employing an approach grounded in Islamic values such as ukhuwah (brotherhood), tasamuh (tolerance), and islah (reconciliation), as well as local wisdom such as musyawarah (deliberation) and gotong royong (cooperation). This study contributes by offering an integrated model that combines religious values and socio-cultural wisdom as a strategic framework for sustainable conflict management. This approach has proven effective in mitigating conflicts and fostering long-term reconciliation among communities.